Husband and Wife Communication Patterns in Periode Baby Blues Syndrome - Yusniawati, Dessy; Ganiem, Leila Mona (Journal of Dialogos, 2024)
This study focuses on interpersonal communication in married couples, especially during the period of baby blues disorder. The approach used is social penetration theory. The study aims to describe the interpersonal communication patterns formed through the process of communication and support in husband and wife relationships during the period of baby blues syndrome. The case study method was used with data collection through interviews with five women who had given birth for the first time and had experienced postnatal baby blues disorder. The results showed that the interpersonal communication process in this period is usually started by the wife with an attitude of self-opening. Through interaction with the husband, the wife defines the form of support provided by the husband, both verbally and non-verbally, as a positive reaction to the self-opening that has been done. This communication pattern forms a cycle in each couple, showing that the four couples tend to have balanced and equal communication patterns. Husbands were involved mainly in providing instrumental support related to childcare and household activities. However, in one other couple, the communication pattern was considered unbalanced due to the lack of support from the husband, so the wife sought support from her female friends who also experienced similar baby blues.